Dictionary of Qumran Aramaic - Cook, Edward M. (Eisenbrauns, 2015)
Intro -- Contents -- Introduction -- Acknowledgments -- Abbreviations -- א -- ב -- ג -- ד -- ה -- ו -- ז -- ח -- ט -- י -- כ -- ל -- מ -- נ -- ס -- ע -- פ -- צ -- ק -- ר -- שׁ -- שׂ -- ת -- Bibliography of Works Cited.